Development of LKPD based on Cognitive Conflict on Caloric Material to Improve Concept Understanding of Class XI Students of SMAN 1 Padangpanjang - Hanifah, Khonisa (PILLAR OF PHYSICS EDUCATION, 2025)
Misconceptions occur because students construct their own ideas from their surroundings without professional help, so misconceptions are caused by students' original knowledge that differs from professional opinion.  The purpose of this study is to develop cognitive conflict-based LKPD in order to correct misconceptions and enhance students' comprehension of the subject matter.  Preliminary research, development or prototyping, and assessment are the three phases of the Plomp model, which is used in this kind of design or development study.  The development process in this study is restricted to the Expert Review stage of the Develop or Prototyping Phase. Preliminary research was conducted by conducting observations and concept understanding tests on the problem of misconceptions among students on the concept of heat.  The design of LKPD, self-evaluation, and expert review of LKPD prototypes were completed throughout the development phase.  Three physics instructors' validation sheets and the researchers' own self-evaluation assessment sheets provided the data.  Preliminary research revealed that students' notions of heat material were difficult to understand.  Consequently, a LKPD based on cognitive conflict was created in order to enhance students' comprehension of concepts.  With an average score of 96%, the LKPD design's self-evaluation findings indicate that it falls into the very good category.  With an average score of 0.89, the expert evaluation results indicate that the LKPD's design falls into the very valid category.